Exploring community satisfaction in building an innovative android-based mobile survey application for people travelling to Mentawai Island - Nazarwin, Nazarwin; Hasnur, Juliandri; Kurniawan, Edi (Jurnal Pendidikan Teknologi Kejuruan, 2024)
This research aims to develop and evaluate an android-based mobile survey application to measure passenger satisfaction with transportation service standards to Mentawai Island. The application that has been developed will help in the evaluation process so that the improvement of sea transportation services can be improved. This study used the 4D development model and involved 30 passengers of the Mentawai Fest Ship as research subjects. The research instruments used were a validation questionnaire and a practicality test. A survey of public satisfaction with transportation services to Mentawai Island using an Android-based application will be developed, implemented, and evaluated. The results show that the application effectively meets the community's needs, shows high validity, and provides a convenient feedback mechanism for users. Overall, these findings contribute to efforts aimed at improving the quality of transportation services and the overall passenger experience.